Compatibility of Site-Specific Recombination Units between Mobile Genetic Elements - Suzuki, Shota; Yoshikawa, Miki; Imamura, Daisuke; Abe, Kimihiro; Eichenberger, Patrick; Sato, Tsutomu (iScience, 2020)
Site-specific recombination (SSR) systems are employed for transfer of mobile genetic elements (MGEs), such as lysogenic phages and integrative conjugative elements (ICEs). SSR between attP/I and attB sites is mediated by an integrase (Int) and a recombination directionality factor (RDF). The genome of Bacillus subtilis 168 contains SPβ, an active prophage, skin, a defective prophage, and ICEBs1, an integrative conjugative element. Each of these MGEs harbors the classic SSR unit attL-int-rdf-attR. Here, we demonstrate that these SSR units are all compatible and can substitute for one another. Specifically, when SPβ is turned into a defective prophage by deletion of its SSR unit, introduction of the SSR unit of skin or ICE converts it back to an active prophage. We also identified closely related prophages with distinct SSR units that control developmentally regulated gene rearrangements of kamA (L-lysine 2,3-aminomutase). These results suggest that SSR units are interchangeable components of MGEs. [Display omitted] •Lysogenic phage-derived SSR unit is sufficient to drive SSR of ICE and vice versa•Defective prophage-derived SSR unit can drive the excision of the active lysogenic phage•Closely related prophages with distinct SSR units control each gene rearrangements•Correspondence between MGEs and their cognate SSR units is not absolute Genetics; Molecular Genetics; Microbiology; Microbial Genetics